Studying novel, natural antimicrobials in food systems - Falcus, Kirsty J. (2019)
The purpose of this project was to test a range of novel, natural antimicrobial compounds provided by Phil Stroud Solutions Ltd to determine their effectiveness for use in food products. The idea behind the project was to develop a ‘clean label’ antimicrobial to have a primary use in meat products. It was hoped that the new antimicrobial would surpass the effectiveness of current antimicrobials being used and be more desirable to a consumer. The antimicrobials were tested against a group of five bacteria including gram positive and gram negative pathogens and spoilage organisms including Listeria, Salmonella, E.coli and Pseudomonas. The antimicrobials were first screened to determine their effectiveness using an absorbance measurement method. They were then tested in sausage and mince products by dipping and incorporation. Safety testing was completed in the form of the Ames test. Results showed that compounds D and E had the most effect on all of the five bacteria in screening and in meat trials. In meat trials the antimicrobials were added to the product before being tested over a number of days. In some instances there was a several log reduction in growth. The Ames test also confirmed that the products are safe for use in food. Overall the novel natural antimicrobials tested have scope to be used in food products in the future.